Development of portable DC water kettle - Syed Sahlan, Syed Shah Minan (2016)
Nowadays, biker like to spend their time with the nature such as visiting waterfall or camping in a jungle where the electric power is not available. This situation have made new technology to be developed such as powerbank and portable lamp. One of the new tachnology that have been developed is electrical portable water kettle. This device help people to boil the water without using fire as the heater. In this thesis, the portable DC water kettle suitable for motorcycle is designed, developed and tested. This device use 12v, 5a battery as it power supply which is directly connect to the source. The reason for choosing this type of battery is because it commonly use by the motorcycle in Malaysia. The kanthal 26 AWG is used as it heating element while the mechanical thermostate will sense the boiled water. The device has been tasted with different length of heating element which are 15cm, 30cm and 50cm corrensponding to resistance value 2.6ohm, 5.0ohm and 8.3ohm respectively. The kanthal is connected to the thermostate by using copper wire. This device can boil 500ml of water at one times. The device also equiped with autooff sensor to cut the power supply when the water reach at it boiling point. Experiment conducted shows that the most optimal condition is achieved when the device uses kanthal 26 AWG, with resistance is at 5.0ohm. With 500ml water in the container, the device took about 25minutes to reach boiling point while maintaining the motorcycle’s batery at healthy condition.